2017
DOI: 10.1021/jacs.7b01439
|View full text |Cite
|
Sign up to set email alerts
|

A Breakthrough Efficiency of 19.9% Obtained in Inverted Perovskite Solar Cells by Using an Efficient Trap State Passivator Cu(thiourea)I

Abstract: It is extremely significant to study the trap state passivation and minimize the trap states of perovskite to achieve high-performance perovskite solar cells (PSCs). Here, we have first revealed and demonstrated that a novel p-type conductor Cu(thiourea)I [Cu(Tu)I] incorporated in perovskite layer can effectively passivate the trap states of perovskite via interacting with the under-coordinated metal cations and halide anions at the perovskite crystal surface. The trap state energy level of perovskite can be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
278
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(295 citation statements)
references
References 72 publications
5
278
1
4
Order By: Relevance
“…Reproduced with permission. [122] Copyright 2017, American Chemical Society. h) The formation of quasi-3D FA x PEA 1−x PbI 3 crystal.…”
Section: Grain Boundaries In the Perovskite Active Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [122] Copyright 2017, American Chemical Society. h) The formation of quasi-3D FA x PEA 1−x PbI 3 crystal.…”
Section: Grain Boundaries In the Perovskite Active Layermentioning
confidence: 99%
“…Owning to the matched valancing band maximum, the trap state passivator/perovskite formed bulk heterojunction (BHJ) facilitated the hole transport and decreased the charge recombination. [122] Jen and coworkers introduced a phenylethylammonium iodide (PEAI) into perovskite, where the PEA + can passivate the defects at lattice surface and grain boundaries and behaving as molecular locks to strengthen the intermolecular interactions of perovskite. [123] In addition, perovskite also suffered from ion migration, and recent studies showed that grain boundaries might be the main sites for this process.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Although the highest certified PCE of PSCs is comparable to that of commercialized silicon photovoltaic devices, the poor long-term stability of PSCs is an unavoidable hurdle to widespread application. The power conversion efficiency (PCE) of PSCs has exhibited an unprecedented rise from the initial 3.8% to over 22% in the past few years.…”
mentioning
confidence: 99%
“…The CuI@TiO 2 devices showed trap densities of 5.76 × 10 15 , 5.49 × 10 15 , and 3.45 × 10 15 cm −3 , and the TiO 2 device showed a trap density of 1.52 × 10 16 cm −3 . [32] Since the recombination rate (hundreds nanosecond scale) is much slower than the extraction rate (tenths nanosecond scale), [43] even if a part of the generated holes moves to CuI, positive CuI can pull the electron to the interface between TiO 2 and perovskite layer with very low recombination. Moreover, the electron mobility of bare TiO 2 and CuI@TiO 2 device is calculated by the SCLC method in Figure 4d.…”
mentioning
confidence: 99%